Adult stem cell and mesenchymal progenitor theories of aging - Fukada, So-ichiro; Ma, Yuran; Uezumi, Akiyoshi (Frontiers in Cell and Developmental Biology, 2014)
Advances in medical science and technology allow people live longer lives, which results in age-related problems. Humans cannot avoid the various aged-related alterations of aging; in other words, humans cannot remain young at molecular and cellular levels. In 1956, Harman proposed the ‘free radical theory of aging’ to explain the molecular mechanisms of aging. Telomere length, advanced glycation, and accumulation of DNA or mitochondrial damage are also considered to be mechanisms of aging. On the other hand, stem cells are essential for maintaining tissue homeostasis by replacing parenchymal cells; therefore, the stem cell theory of aging is also used to explain the progress of aging. Importantly, the stem cell theory of aging is likely related to other theories. In addition, recent studies have started to reveal the essential roles of tissue-resident mesenchymal progenitors/stem cells/stromal cells in maintaining tissue homeostasis, and some evidence of their fundamental roles in the progression of aging has been presented. In this review, we discuss how stem cell and other theories connect to explain the progress of aging. In addition, we consider the mesenchymal progenitor theory of aging to describing the process of aging.